Effects Of Cryostabilizers And Cryoprotectant On Frozen Chinese Steamed Bread Dough - Sim , Sze Yin (2011)
In this study, different food gums (sodium alginates, carboxymethylcellulose, psyllium husk powder, locust bean gum, and konjac glucomannan), maltodextrin, and trehalose were added to preserve frozen Chinese steamed bread (CSB) dough. Dough mixing and stretching properties were analyzed using farinograph and extensograph, respectively. Differential scanning calorimetry (DSC) was used to study the thermal properties of dough upon frozen storage and freeze-thaw cycles. Dynamic mechanical analysis (DMA) was employed to determine the dynamic mechanical properties of dough.